The Effectiveness of Picture Strip Story for Improving Eighth-Grade Students’ Vocabulary Mastery in an EFL Classroom - Andi Mangnguntungi Sudirman; Sri Rahayu; Sri Damayanti; Dirgahayu (Universitas Islam Negeri Palopo, 2023)
Vocabulary knowledge is a foundational component of second/foreign language proficiency because it supports comprehension and production across skills. However, vocabulary learning in many EFL classrooms remains dominated by decontextual memorization that often fails to engage learners and support retention. This study investigated whether Picture Strip Story (a sequence of pictures presented as a short narrative) could improve eighth-grade students’ vocabulary mastery. A quantitative pre-experimental one-group pretest–posttest design was employed. Twenty-seven students were selected randomly from the eighth-grade population. Students completed a vocabulary pretest, received Picture Strip Story-based instruction, and then completed a posttest. The instrument consisted of multiple-choice and word-matching items. Results showed that the posttest mean score (M = 76.67, SD = 7.74) exceeded the pretest mean score (M = 57.59, SD = 10.90). A paired-samples t-test indicated a significant improvement, t(26) = 11.744, p < .001, with a large effect size (Cohen’s dz = 2.26). These findings suggest that Picture Strip Story can be an effective instructional medium for vocabulary learning by providing contextualized input and visual support. Implications for classroom practice and recommendations for future research are discussed..